31 PATIENTS WITH REFRACTORY HYPERCHOLESTEROLEMIA HAVE POOR OUTCOME AFTER HEART TRANSPLANTATION. (1st January 2005) - Nakashima, J. K.; Kobashigawa, J. A.; Patel, J. K.; Yamada, C.; Hamilton, M.
Abstract : Background: Hypercholesterolemia is common after heart transplantation and is seen in 60-80% of all patients. HMGCo-A Reductase Inhibitor (Statin) therapy is effective in cholesterol lowering and has been associated with a significant survival benefit and reduction in transplant coronary artery disease (TCAD) following heart transplantation. TCAD is seen in approximately half of heart transplant patients within 5 years and is the major limiting factor in long-term survival. In the general population hypercholesterolemia is associated with increase incident of cardiovascular mortality. It is not known if hypercholesterolemia refractory to statin therapy also has poor outcome in heart transplant recipients. Methods: We retrospectively reviewed 261 patients transplanted between 7/97 and 9/01. Of those patients, 187 survived to 12 months. The majority of patients (90%) were treated with statins. We averaged the total cholesterol levels at 3, 6, and 12 months and divided patients into 3 groups: 1) Cholesterol ≤ 200 (n=108), 2) Cholesterol 201-250 (n=69), or 3) ≥ 250 (n=10). Patient groups were assessed for 3-year survival and the development of TCAD. Results: Age at transplant, sex, race, ischemic time, donor age, and donor sex was similar among the three groups. All patients in ≥250 group were on statins. 90% were on statins in the two other groups. There was significantly less survival at three-years for patients in the ≥250 group (70% vs. 97% vs. 88%, p=0.012). There was no difference in the causes of death between the groups. The ≥250 group also had less freedom from TCAD at three-years (67% vs. 79% vs. 75%) which did not reach statistical significance. Conclusion: Hypercholesterolemia refractory to statin therapy appears to be a marker for poor outcome after heart transplantation. Alternative strategies to lower cholesterol in these patients are needed.